2002
DOI: 10.1073/pnas.192276599
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing grain yields reduces CH 4 emissions from rice paddy fields

Abstract: Microbial production in anoxic wetland rice soils is a major source of atmospheric CH4, the most important non-CO2 greenhouse gas. Much higher CH4 emissions from well managed irrigated rice fields in the wet than in the dry season could not be explained by seasonal differences in temperature. We hypothesized that high CH4 emissions in the wet season are caused by low grain to biomass ratios. In a screenhouse experiment, removing spikelets to reduce the plants' capacity to store photosynthetically fixed C in gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(73 citation statements)
references
References 26 publications
3
69
0
1
Order By: Relevance
“…Bronson et al (1991) reported that the slow release of acetylene from urea-encapsulated calcium carbide significantly reduced CH 4 and N 2 O emissions during rice cultivation and increased rice yield. Rice grain yield was negatively correlated with seasonal CH 4 flux (Table 3), which was supported by Denier van Der Gon et al (2002). The increased carbon sources in paddy soil enhanced CH 4 emissions but decreased N 2 O emissions were observed under anaerobic conditions (Hou et al 2000).…”
Section: Discussionmentioning
confidence: 57%
“…Bronson et al (1991) reported that the slow release of acetylene from urea-encapsulated calcium carbide significantly reduced CH 4 and N 2 O emissions during rice cultivation and increased rice yield. Rice grain yield was negatively correlated with seasonal CH 4 flux (Table 3), which was supported by Denier van Der Gon et al (2002). The increased carbon sources in paddy soil enhanced CH 4 emissions but decreased N 2 O emissions were observed under anaerobic conditions (Hou et al 2000).…”
Section: Discussionmentioning
confidence: 57%
“…During cropping season of 2014, significant associations were noted under rainfed rice (R 2 = 0.87) ( Table 4). Denier van der Gon et al 38 reported a negative correlation between grain yield and CH 4 emissions. This could be due to the availability of more photosynthetic C as root exudates, since it was not being used in seed production.…”
Section: Influence Of Ghg Fluxes On Rice Productivitymentioning
confidence: 99%
“…Gas samples for flux measurements occurred on approximately weekly intervals at 7,14,21,28,35,43,49,56,63,71, and 77 days after flooding (DAF) for the flooded duration of the study. Sampling intensity was increased after flood release to 80, 82, 83, 84, and 85 DAF [i.e., 2, 4, 5, 6, and 7 days after flood release (DAFR)] in an attempt to adequately quantify a post-flood-release pulse of CH4 that has commonly been observed in previous studies [32,48,49,51,54,55,56].…”
Section: Gas Sampling and Analysismentioning
confidence: 99%
“…Research conducted by Denier van der Gon et al [63] indicated that CH 4 emissions are related to allocation of photosynthetically derived C between roots and grains and that decreasing translocation of C to grains (i.e., removing florets prior to grain fill) causes an increase in C translocation to roots and an increase in CH 4 emissions. Sass and Cicerone [64] also determined a link between grain filling and methanogenesis, where increasing CH 4 emissions occur as conditions become more unfavorable for spikelet formation, thus decreasing the grain-sink for photosynthates.…”
mentioning
confidence: 99%